Adsorption of Remazol Blue And Indigosol Yellow Mixed Dyes Using Bidara Arab Leaves (Ziziphus spina-christi) - Kurnia, Mega; Suprapto, Suprapto; Ni'mah, Yatim Lailun (Indonesian Journal of Chemical Analysis (IJCA), 2024)
In this study, the adsorption of Remazol Blue and Indigosol Yellow using Bidara Arab leaves (Ziziphus spina-christi) as adsorbents was investigated through batch adsorption. The experimental parameters included contact time, adsorbent mass, initial concentrations, and pH. UV-Vis spectrophotometer was employed to measure the adsorption results at the maximum wavelength of each dye. The research was conducted in triplicate, and a t-test, "Paired Two Sample for Means", with a standard deviation <2% was employed for statistical analysis. Optimal adsorption conditions were achieved at a contact time of 45 minutes, an adsorbent mass of 45 mg, an initial concentration of 30 ppm, and a pH of 3. The results indicated that Bidara Arab leaves effectively reduced the concentration of the mixed dyes with %decoloration up to 99,79% on Remazol Blue and 99,50% on Indigosol Yellow.